My science book of senses - Ardley, Neil. (London : New York : Doorling Kindersley, 1992)
Part of a series of practical activity books, that include experiments, this book looks at the five senses. Each book of the series introduces a science concept through projects that can be carried out at home. The book also includes tricks and puzzles, together with toys and models to make.
Keywords: My science book of senses